The Effectiveness of Group Guidance in Addressing Bullying Issues at Sanggar Malaysia - Dedek Rahmawati; M Fauzi Hasibuan (INDONESIAN COUNSELING AND PSYCHOLOGY, 2026)
Bullying is a social problem that can negatively affect the emotional, psychological, and social development of elementary school students. This study aims to analyze the effectiveness of group guidance services in addressing bullying problems among students at Sanggar Malaysia. The research employed a quantitative method using a pre-experimental approach with a One-Group Pretest–Posttest design. The research subjects consisted of six sixth-grade students who were identified as experiencing or being involved in bullying behavior and were selected using a purposive sampling technique. Data were collected using a bullying behavior questionnaire administered before and after the implementation of the group guidance service. Data analysis was conducted using statistical tests to determine differences in the level of bullying behavior before and after the intervention. The results of the study showed a significant decrease in bullying behavior after the participants took part in group guidance activities, which was indicated by increased social awareness, greater empathy toward peers, and improved ability to control aggressive behavior. These findings indicate that the group dynamics created during the guidance process allowed participants to share experiences, understand the impact of bullying behavior, and develop more positive social attitudes. Therefore, it can be concluded that group guidance is an effective intervention strategy for addressing bullying problems in non-formal learning environments such as Sanggar Malaysia. The results of this study are expected to encourage readers to reflect on the role of group guidance services as a potential preventive and curative approach in creating a safe, empathetic, and bullying-free educational environment.